THE IMPACT OF THE DETERMINANTS FOR THE SUPPLY OF SUGAR AND ALCOHOL IN BRAZIL WITHIN THE PERIOD OF 1995 TO 2009 - Bertotti, Gustavo; Massuquetti, Angélica; Lelis, Marcos Tadeu Caputi (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This study has the objective to measure the impact of the determinants for the supply of sugar and alcohol in Brazil, with the intention to capture the duration of the osclillations of prices and production influences to the Brazilian market. The econometric model proposed for the following study consists of a vector auto-regressive model with an error correction mechanism based on quarterly temporal series within the period of 1995 to 2009. Afterwards, it was analyzed through Granger causality tests and the impulse response function (IRF) the precedence among the variables comprehended in the models, as well as the impulse that a variable applies over the others. At last based on the tests presented it has got to the conclusion that the model B with four lags, showed the most coherent and conclusive results concerning the theoretical support and the dynamics of the sector. Among the main results it is evident the positive relationship of sugar and ethanol concerning the determination of its offers, at the sense that the increase one product generates, at the same point, the expansion of the other. In addition the behaviors of the variables of prices, in part presented results in agreement to the expected signals. The sugar exports and exchange rate impact positively in the income received by the producer and infer positively for the expansion of the Brazilian sugar offer.